Treatment of High-Impact Injuries of Thoracic and Lumbar Spine - M. K. Sabyraliyev; Z. D. Sulaymanov; T. B. Minasov; R. A. Saubanov; N. N. Aslyamov; R. F. Fayzullin; V. A. Fadeyev; Yu. M. Malsagov (Креативная хирургия и онкология)
Introduction. Surgical treatment of patients with spinal injuries with traumatic spinal canal stenosis is an important and widely discussed problem of contemporary vertebrology. Injuries to the spine in the incidence structure of isolated or combined injuries occupy a special place due to their high social and clinical significance. Long-term outcomes of traumatic disease in patients with combined trauma to the thoracic and lumbar spine are studied, as before, by ever larger groups of researchers in connection to the new generations of spinal fixation devices being introduced.Materials and methods. 111 patients with various thoracolumbar spine injuries treated surgically were included in the study. In 40 patients, the post-traumatic stenosis was treated with the use of ligamentotaxis and transpedicular osteosynthesis. Thll–Thl2, Th12–L1 and L1–L2 were the most frequent localisations of the level of injury in the study group.Results and discussion. The immediate treatment outcomes observed were as follows — good in 33 (82.5%) cases, satisfactory in 6 (15.0%), unsatisfactory — in 1 (2.5%). Long-term outcomes with follow-up longer than a year were recorded in 27 (67.5%) patients with good outcomes in 20 (74.1%) and satisfactory in 7 (25.9%).Conclusion. A correct stabilisation with metal systems makes it possible to verticalize the patient quickly and shorten the rehabilitation period in all patients including those of active working age, as well as minimize the risks in the long term.